JOB CHARACTERISTICS AND JOB SATISFACTION AMONG POLICE OFFICERS IN ENUGU URBAN. - Obodo, Paul A; Okonkwo, Ejike A; Aboh, Uche J (Practicum Psychologia, 2019)
Considering the theoretical assumptions of the affect model linking job characteristics to job satisfaction, this cross-sectional survey investigated job characteristics as predictors of job satisfaction among one hundred and ninety (190) police officers in Enugu urban comprising 125 males and 65 females between the ages of 20 to 59 years (M = 36.83, SD = 6.07) sampled using multi-stage sampling (cluster and systematic sampling techniques). The 21-item Job Characteristics Scale (Hackman & Oldham, 1975) and 20-item Minnesota Satisfaction Questionnaire (Weiss, Dawis, England & Lofquist, 1967) were administered for data collection. Application of multiple regression as statistical test revealed that job characteristics jointly predicted job satisfaction, R2 = .09, F = 2.63, P < .05 level of significance, whereas only autonomy independently predicted job satisfaction, β = .61, t = 3.42, at p <.05 level of significance, hence the need for policy makers in Nigeria Police Service Commission to consider job characteristics especially job autonomy in order to enhance job satisfaction of police officers. The findings were discussed in the light of previous studies.